دور تكنولوجيا المعلومات والاتصال في تعزيز التشارك المعرفي للطاقم الطبي -دراسة حالة مستشفى محمد الصديق بن يحيى جيجل- - فدسي, فاطيمة; نجيمي, عيسى (جامعة الوادي - University of Eloued, 2022)
The aim of the study is to know the role of Information and Communication Technology in improving the knowledge sharing of the medical staff in Jijel Hospital. To achieve the objectives of this study, a questionnaire was distribute a sample of 80 doctor and paramedic, moreover we followed the descriptive analytical method to illustrate the theoretical and applied side of the study, the questionnaire was used as a basic study tool to collect data, and the statistical package for social sciences “spss” was used for processing the results. The results of this study have demonstrated that indeed, there is a low use of information and communication technology among the medical staff, in addition the level of knowledge sharing is high, it was also there is a positive and statistically significant relationship between the use of information and communication technology and the knowledge sharing among the medical staff at Muhammed El Siddik Ben Yahya hospital in Jijel at the level of 0,05.
The role of information and communication technology in improving the knowledge sharing among medical staff –Case study of Mohamed Siddik Ben Yahya Jijel Hospital
مقال
Keywords: تكنولوجيا المعلومات والاتصال ; التشارك المعرفي ; عمليات التشارك المعرفي